BTN House Marketing System In Islamic Economic Perspective Case Study In Pt. Jaya Jaya Graha Jempong Baru Mataram - Nur Fitri Hidayanti; Abdul Wahab; Zaenafi Ariani (Proceedings of The ICECRS, 2020)
Nowadays, the areas around Mataram City are seldom encountered by rice fields, because almost all of the land is built into housing which was built by developers and offices built by government and private institutions. BTN housing itself is very much in demand. The marketing system conducted by PT. Citra Jaya Graha in selling its products using a marketing mix. First, PT. Citra Jaya Graha in providing its products in the form of BTN houses prioritizes quality by providing various types of houses. Second, in determining price, PT.Citra Jaya Graha to vary the BTN house that he built according to the type based on the price difference seen from the model of the house, type of BTN house (land area and building area), material prices and the cost of building the BTN house. Third, PT. Citra Jaya Graha in promoting products produced using billboards, brochures, and employees (marketing), print media (Lombok Pos newspaper) and electronic media such as websites and Facebook. Fourth, the process of distributing BTN houses is done directly, marketing offers directly to prospective buyers. PT. Citra Jaya Graha also built an Islamic housing complex. Like, Griya Sakinah housing and the establishment of a mosque or mosque in several housing complexes that had built.